Trend Information System Research Topics in the SINTA Journal for the Period 2015-2019 - Lailatul Muniroh; Dwi Rolliawati; Yusuf Amrozi (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Information systems discipline has developed rapidly over time. Based on 533 information systems study programs in Indonesia, it is possible to have a variety of information systems research topics. However, there is no research on information system topic trends in Indonesia. So, this research aims to determine the trend of research topics in the field of information systems in Indonesia in 2015-2019 based on the publication of the journal SINTA. The method used is qualitative non-interactive. Based on the analysis of documents on the results of data collection on the Google Scholar database using the Publish or Perish tools, the research adopted the recommended PRISMA in improving the quality of systematic reviews and better readers' understanding. The determination of the research topic was based on the abstract content,  keywords and referred to the IS ACM Curricula and previous research. The results of this study can be used as academic references in gaining new insights into the field of information systems. The results of the study based on 1917 raw data obtained from data collection in the journal publication SINTA 2, SINTA 3, and SINTA 4 showed that the topic "Application Development" was a trending topic with the highest percentage, namely 31%, the topic of "Decision Support System" 11% and "System Analysis and Design "10%. The new issues that arose were "Internet of Things", "Machine Learning" and "Artificial Intelligence". Information systems research in Indonesia varies widely, although some studies have a low percentage.